Law's Poverty - Modiri, Joel M (My University, 2015)
This article adopts an analysis that explicitly politicises poverty and relates it to the concrete history of racialised capitalism and structural inequality that defined colonialism and apartheid and continues to persist and intensify in "post"-apartheid South Africa. Rather than formulating racialised poverty in legalist, economist or managerial terms, it should rather be understood as a form of oppression that comprises exploitation, marginalisation, powerlessness, cultural imperialism and violence. Such a formulation would make social structure, historical injustice and power central and would also allow for poverty to be grasped beyond a purely distributive logic by bringing to light the non-distributive, non-economic dimensions of poverty. Comprehending poverty in this way, as not only a question of economic distribution and empowerment, but also one of ethical, moral and even ontological recognition necessitates an enquiry into the emancipatory force of rights. Given their centrality in political and social discourse and in legal scholarship on poverty, it is worth considering whether and to what extent rights can be utilised in the struggle against (racialised) poverty.
Keywords: Racialised poverty; Oppression; Imaginary domain; Precarity; Theories of justice; Rights discourse; Critical theory